Letter from Congressman William F. Ryan - William F. Ryan:::::: (1968)
A letter in which Congressman William F. Ryan describes his bill, H.R. 17331, proposing a guaranteed annual income for all Americans. The plan would create a Bureau of Income Maintenance to provide monthly payments based on income deficiency, offering about $2,000 annually for a family of four with no earnings. Ryan argues the proposal would aid millions living in poverty, serve as a substitute for welfare rather than jobs, and cost an estimated $4.1 billion per year. He urges delegates to support including a guaranteed income plank in the party platform.